An Empirical Analysis of Unconscious Bias in Hiring Practices - Polanco Quintero, Sarah (2024)
The focus of this thesis is on the effects of ethnicity and type of work experience (local versus foreign) on hiring outcomes in the recruitment processes in the Czech labor market with particular attention to the impact of unconscious bias. Six fictitious CVs representing candidates of Czech, Latin American, and Arab ethnicities, with or without work experience were submitted to job postings in Prague, using a correspondence test methodology. Using probit regression the analysis found that there was a significant ethnic bias for Czech applicants and no significant effect for type of work experience on response rates. Increased workforce diversity does not eradicate systemic discrimination on ethnicity in recruitment, as these findings reveal. Recommendations include bias-reduction strategies that can be implemented, namely structured interviews, blind hiring, and more equitable hiring practices overall. Given this fact, the study contributes to knowledge on unconscious bias within a Central European context, as well as to reinforced need for the application of inclusion policies in recruitment.